2015
DOI: 10.1155/2015/129764
|View full text |Cite
|
Sign up to set email alerts
|

Copper-64 Dichloride as Theranostic Agent for Glioblastoma Multiforme: A Preclinical Study

Abstract: Glioblastoma multiforme (GBM) is the most common primary malignant brain tumor in adults with a median survival time less than one year. To date, there are only a limited number of effective agents available for GBM therapy and this does not seem to add much survival advantage over the conventional approach based on surgery and radiotherapy. Therefore, the development of novel therapeutic approaches to GBM is essential and those based on radionuclide therapy could be of significant clinical impact. Experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 14 publications
1
50
0
Order By: Relevance
“…Preclinical studies using [ 64 Cu]CuCl 2 as a theranostic agent in selected human cancer xenograft models in mice, such as glioblastoma multiforme (U-87MG) and malignant melanoma (B16F10, A375M), demonstrated its potential as a therapeutic agent [5, 6]. A case report study of Valentini et al evaluated the potential of [ 64 Cu]CuCl 2 as a therapeutic agent in two patients with metastatic prostate and uterine cancer, respectively [7].…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies using [ 64 Cu]CuCl 2 as a theranostic agent in selected human cancer xenograft models in mice, such as glioblastoma multiforme (U-87MG) and malignant melanoma (B16F10, A375M), demonstrated its potential as a therapeutic agent [5, 6]. A case report study of Valentini et al evaluated the potential of [ 64 Cu]CuCl 2 as a therapeutic agent in two patients with metastatic prostate and uterine cancer, respectively [7].…”
Section: Introductionmentioning
confidence: 99%
“…For its elusive response to standard treatments, the development of novel therapeutic approaches for GBM remains indeed a pivotal step in the modern oncologic research. Protocols based on radionuclide therapy appear to be particularly promising for the GBM treatment [2,[4][5][6][7]. Experimental evidence has clearly demonstrated that cancer cells have a particularly high fractional content of copper inside the cytoplasmic and nuclear fraction compared to normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several positron-emitting radionuclides with a high atomic number and/ or a long half-life have been proposed both for imaging and therapeutic approach. Among these, Cu radioisotopes seem to be significantly interesting [1,4,11,12]. Cu radioisotopes, as a group, comprise radioisotopes which, due to their emission properties, may be applied both for diagnostic studies ( Cu) [13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, its particulate emissions coupled with an intermediate physical half‐life of 12.7 h also makes 64 Cu a potential agent for internal radionuclide therapy. In its chemical form, copper dichloride: [ 64 Cu] CuCl 2 has demonstrated potentials for imaging and treating glioblastoma and malignant melanoma in preclinical studies, based on its affinity toward human copper transporters . Preliminary human studies have also been performed with positive outcomes, as measured by tumor volume reduction, for treating prostate cancer and uterine cancer in two patients using 3,700 MBq of [ 64 Cu] CuCl 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In its chemical form, copper dichloride: [ 64 Cu] CuCl 2 has demonstrated potentials for imaging and treating glioblastoma and malignant melanoma in preclinical studies, based on its affinity toward human copper transporters. 2,3 Preliminary human studies have also been performed with positive outcomes, as measured by tumor volume reduction, for treating prostate cancer and uterine cancer in two patients using 3,700 MBq of [ 64 Cu] CuCl 2 . 4 64 Cu can also be labeled with chelators which can be linked to monoclonal antibodies, proteins, peptides, and nanoparticles to image and treat a variety of clinical conditions and diseases.…”
Section: Introductionmentioning
confidence: 99%